Correlation of Total Bacterial and Vibrio spp. Populations between Fish and Water in the Aquaculture System - Kim, Ji Yeun; Lee, Jung-Lim (Frontiers in Marine Science, 2017)
Fish-borne illness is associated with pathogenic bacteria, Vibrio spp., transmitted from contaminated aquaculture water to fish. But little is known about the correlation between water quality in aquaculture and subsequent bacterial contamination in fish products. The degree of bacterial transmission from Vibrio spp. contaminated aquaculture water to fish was investigated. V. anguillarum, V. parahaemolyticus, and V. vulnificus were administered to aquaculture water and the amounts of Vibrio spp. and total bacteria in the aquaculture water and fish filets were assessed using a multiplex real-time PCR assay. Following the challenge, the counts of total bacteria and Vibrio spp. simultaneously increased in both the water and fish filets with levels of bacteria in the fish directly proportional to that in the water. The total bacterial population in the water decreased to pre-challenge levels over time. However, Vibrio spp. counts in fish filets were nearly unchanged during the same time period. There is a strong correlation between the amount of bacteria that are present in aquaculture waters and those that can be observed in the subsequent fish muscle tissue. In addition, the numbers of Vibrio spp. in the random sampled aquaculture fish filets were highly associated with the levels in the aquaculture water. Consequently, populations of total bacteria and Vibrio spp. in aquaculture water is highly correlated with bacterial number of aquacultured fish product, therefore the surveillance of Vibrio populations in the aquaculture water could be an indicator of the microbial contaminations of fish filets.